Investigation on the products distribution, reaction pathway, and discharge mechanism of low‐pressure CO2 discharge by employing a 1D simulation model. Issue 6 (1st April 2021) - Wang, Cong; Fu, Qiang; Chang, Zhengshi; Zhang, Guanjun
Abstract: Mars has a special carbon dioxide environment. The surface and atmosphere of Mars contain a large amount of solid and gaseous carbon dioxide, which makes the in‐situ resource utilization of Martian carbon dioxide attract widespread attention. The conversion of carbon dioxide into fuel or high value‐added products through electrical discharge has become a research focus, in which numerical simulation is one of the important means to explain the experimental phenomenon and the mechanism. Therefore, a one‐dimensional fluid model was established in this paper to simulate the discharge and conversion of carbon dioxide under simulated Martian atmospheric pressure. The discharge mode, particle distribution, and discharge mechanism were studied by considering CO2 vibrational states and vibration relaxation reaction in the model. The results show that the discharge mode is glow discharge with an obvious cathode fall region, negative glow space, and positive column. The density of the four discharge products, C, O2, CO, and O, shows a step‐up trend, showing a significant cumulative effect, and the peak values appear near both electrodes. The density of vibrational states of CO2 molecule, which is highest in the neutral products, increases during the discharge stage and decreases after the discharge is extinguished. The temporal and spatial distribution of reaction rates shows that vibrational excitation, electronic excitation, and vibrational relaxation reactions dominate the loss and formation of CO2 . The density of ground‐state CO2 decreases obviously in the discharge stage, and the minimum density appears near the instantaneous cathode. After the discharge is extinguished, the CO2 near the instantaneous cathode increases gradually. Abstract : CO2, which widely exists in Martian atmosphere, can be converted into O2 and fuel in‐situ for supporting the construction of Mars energy base. We use the plasma technology to activate CO2 molecules under mild conditions and generate the oxygen and the carbon monoxide. The discharge mode, particle distribution and discharge mechanism were studied, which will be helpful for further work about the in‐situ utilization of CO2 resources on Mars and the carbon emissions governance on Earth side.